Study of Multiple Photoneutron Reactions on 197Au Induced by 2.5 GeV Bremsstrahlung - Hien, Nguyen Thi; Khue, Pham Duc; Thanh, Kim Tien; Do, Nguyen Van (Communications in Physics, 2013)
We identified eight radionuclides \(^196\)Au, \(^195\)Au, \(^194\)Au, \(^193\)Au, \(^192\)Au, \(^191\)Au, \(^190\)Au, \(^189\)Au formed via the multiple photoneutron reactions \(^197\)Au\((γ ,kn)^197 - k\)Au with 2.5 GeVbremsstrahlung. The yields of radionuclides that decay by emitting \(γ \)-ray were measured using high purity germanium (HPGe) detector coupled to a PC-based multichannel analyzer. In order to improve the accuracy of the experimental results the necessary corrections were made. The obtained results are compared with reference data and the variations of the \(^197\)Au(\(γ \),kn)\(^197 - k\)Au reaction yields according to incident bremsstrahlung energy and neutron multiplicity are also discussed